Christianity and Duterte’s War on Drugs in the Philippines - Cornelio, Jayeel (Archīum Ateneo, 2019)
The War on Drugs defines Rodrigo Duterte’s presidency in the Philippines. Although thousands have been killed since 2016, it continues to enjoy strong public support. How does Christianity respond? This question is pertinent given that religion has played a prominent role as a civil society actor in the country. The study interrogates how leaders of various Christian groups frame the War on Drugs in Payatas, an urban poor hotspot. Our argument is that the way a religious community responds to the War on Drugs is heavily informed by how it understands the nature of the drug user. They are either sinful human beings or victims of wider social injustices such as poverty. Many religious leaders view them as sinners whose ‘wickedness’ and criminal acts need to be eradicated. Towards the end of the article, we explain this distinction and suggest that the dominant view that drug users are sinners hints at an implicit religious underpinning for the popular support for the War on Drugs.